1988
DOI: 10.1007/bf01262776
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation einer Spenderleber auf zwei Empf�nger (Splitting-Transplantation) - Eine neue Methode in der Weiterentwicklung der Lebersegmenttransplantation

Abstract: Tumor surgery in this field is no longer such a high risk as previously. Prolonged survival can be achieved by resection of hepatocellular carcinomas in non-cirrhotic livers (3-year survival 58%, n = 54 patients) and for colorectal liver metastases (3-year survival 44%, n = 124 patients). But surgery is rarely successful for the most frequent type of liver malignancy, the hepatocellular carcinoma in cirrhosis. Central bile duct carcinomas are now resected more frequently than in the past. Liver grafting seems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
102
0
15

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 537 publications
(117 citation statements)
references
References 3 publications
0
102
0
15
Order By: Relevance
“…Atualmente esse método encontra limitações pois restringe a utilização de enxertos para receptores adultos, cujas indicações de transplante são mais numerosas do que nas crianças 15 . Em 1988, Pilchmayr e col. 16 introduziram a técnica conhecida como split liver transplantation. Neste método, o fígado de um doador cadáver é dividido em duas partes que são implantadas em 2 receptores aumentando, portanto, a disponibilidade de enxertos.…”
Section: Discussionunclassified
“…Atualmente esse método encontra limitações pois restringe a utilização de enxertos para receptores adultos, cujas indicações de transplante são mais numerosas do que nas crianças 15 . Em 1988, Pilchmayr e col. 16 introduziram a técnica conhecida como split liver transplantation. Neste método, o fígado de um doador cadáver é dividido em duas partes que são implantadas em 2 receptores aumentando, portanto, a disponibilidade de enxertos.…”
Section: Discussionunclassified
“…Two techniques have been used for split liver transplantation, i.e., ex vivo, splitting the liver on the bench after removal from the cadaver, and in vivo (in situ), division of the liver in the cadaver before procurement. The first split liver transplantation was reported by Pichlmayr et al in 1988, 82 and the first expanded series of 30 patients was reported by Broelsch et al 83 In this early experience using the ex vivo technique, results were poor with only 67% of adults and 20% of children surviving, and there was a high rate of complications, particularly biliary, and reoperations. In a report from the European Split Liver Registry by DeVille et al 84 of 50 donors yielding 100 grafts, the adult graft and patient survival rates were 72% and 80%, respectively, in elective UNOS status 2B and 3 patients and 56% and 68%, respectively, in urgent UNOS status 1 or 2A patients.…”
Section: Split Liver Transplantationmentioning
confidence: 99%
“…Em particular, na técnica de bipartição do fígado, com um fígado podemos obter dois enxertos (lobo direito e lobo esquerdo hepático), beneficiando, assim, dois receptores, técnica desenvolvida por PILCHLMAYR et al (33) .…”
Section: Introductionunclassified
“…O estudo detalhado da anatomia das estruturas do fígado tanto intra, como extra-hepáticas (8,11,12) permitiu, nos últimos anos, o desenvolvimento com sucesso de técnicas alternativas de transplante hepático, como o transplante de fígado reduzido (2,4,32) , o chamado "split-liver" ou bipartição hepática (33) e recentemente o ransplante intervivos (34) .…”
Section: Introductionunclassified